Photocatalysis of Ag-loaded MgTiO3 for degradation of Fuchsin dye and dyes present in textile wastewater under sunlight - Tiwari, Vishal (My University, 2024)
Our research focuses on the fabrication of MgTiO3 by a sonochemical approach and improving its photocatalytic characteristics by loading it with Ag metal. This change allows the photocatalyst to efficiently absorb broad-spectrum solar light while also effectively separating charges, which are critical for photocatalysis. Both MgTiO3 and Ag-MgTiO3 were discovered to exhibit spherical shapes, with Ag showing as smaller spheres and MgTiO3 as bigger ones. The Ag-MgTiO3 photocatalyst effectively degraded Fuchsin dye (Fuc) under solar light exposure, achieving a rate constant of 0.0314 min−1 over 50 minutes. Comparable tests with visible and UV light produced lower Fuc breakdown rates of 87% and 62.3%, respectively, highlighting direct sunlight as our catalyst's most effective light source (99.2%). Even at low concentrations (0.3 g/L), Ag-MgTiO3 demonstrated excellent efficiency. Its photocatalytic activity substantially outperformed typical market options for TiO -P25 powder, 2 which only achieved 42% removal of fuc dye. The catalyst had a zero charge surface pH of 4.46 and achieved maximum Fuc decomposition efficiency at pH 7. Reusability experiments showed the catalyst’s high stability, with an 81.8% Fuc degradation efficiency after five repetitions. Scavenger studies emphasized the crucial role of O2 •- active species in the photodecomposition process, including DMSO, a marked alteration lowering Fuc degradation effectiveness to 37.5 percent. Additionally, Ag-MgTiO3 showed a remarkable 67.8% reduction in total organic carbon (TOC) for Fuc Dye. HRMS demonstrated the formation of simpler intermediates during contaminant degradation. Ag-MgTiO3, with its simple synthesis method and outstanding performance, is a promising alternative for eliminating persistent pollutants in textile wastewater systems.
Keywords: Ag laded MgTiO2 photocatalyst; Photocatalytic activity of Ag-MgTiO3; Photodegradation of Fuchsin dye; Textile dye degradation; Visible/sunlight irradation